مسؤولية الساحر عن إلحاق الضرر بالمسحور: دراسة تحليلية مقاصدية - شريف، سدرة الشريف مصطفى محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This dissertation aims to study the effect and responsibility of sorcerers for the harm that befalls their victims. It also aims to analyse the jurisprudential rulings on sorcery in light of the noble Objectives of Sharia (maqāṣid). These aims are rarely examined in the Islamic literature on sorcery. The dissertation investigates the development and role of sorcery in ancient societies before highlighting the responsibility of sorcerers for the harm they cause in society. The Objectives of Sharia were used to underline the dangers of sorcery and how it undermines the five necessities of these Objectives. The researcher has followed the inductive approach in tracing and researching relevant topics in original and secondary sources and references, before following the analytical approach to study these sources and references and to analyse the text of interviews. In this regard, the researcher has followed the approach of field studies by conducting interviews with specialist Quranic healers to pinpoint the reality and harm of sorcery and to limit its reach through Islamic, sociological, educational and legal means. Some of the conclusions reached by the researcher includes the fact that sorcery is real and has real effects on individuals and societies. The researcher also concluded that sorcery leads to the destruction of the five necessities of the Objectives of Sharia. This makes it imperative to thwart sorcerers as they are morally and materially responsible in full for the harm they cause. The researcher recommends that governments and officials should address the dangers of sorcery by spreading religious awareness in Muslim societies and by enacting laws to punish sorcery as stated in Islamic law.